2016
DOI: 10.1016/j.ijfoodmicro.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 1-methylcyclopropene on the development of black mold disease and its potential effect on alternariol and alternariol monomethyl ether biosynthesis on tomatoes infected with Alternaria alternata

Abstract: Ethylene is a naturally produced plant regulator involved in several plant functions, such as regulation of fruit ripening. Inhibition of ethylene perception by using 1-methylcyclopropene (1-MCP) slows down the ripening of the fruit maintaining its quality and freshness. The use of 1-MCP is a commercial strategy commonly used in the food industry to extend the postharvest life of several fruits, including tomatoes. To assess how 1-MCP affected infection by Alternaria alternata on tomatoes, three different cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
0
15
0
2
Order By: Relevance
“…Research on microbial VOCs fumigation has demonstrated successful antifungal effects on a large spectrum of pathogenic fungi and bacteria 3,33 . Despite these advances, plant diseases caused by B. cinerea and A. alternata remain a challenge 14,34 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on microbial VOCs fumigation has demonstrated successful antifungal effects on a large spectrum of pathogenic fungi and bacteria 3,33 . Despite these advances, plant diseases caused by B. cinerea and A. alternata remain a challenge 14,34 .…”
Section: Discussionmentioning
confidence: 99%
“…The present study investigated A. pullulans antifungal VOCs against two necrotrophic fungal pathogens; Botrytis cinerea and Alternaria alternata. The two pathogens infect a number of horticultural crops causing both pre and postharvest yield losses worldwide 13,14 . Black mould and grey mould are two plant diseases attributed to A. alternata and B. cinerea respectively 13,14 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The LOQ was deemed to be the lowest concentration that could be quantified reliably. The Cq of the LOQ was determined using the following equation: Estiarte et al (2016). For mycotoxin quantification, working standard solutions were used to perform a ten-point calibration curve (1500, 1250, 1000, 750, 500, 250, 100, 50, 25 and 10 ng/mL).…”
Section: Dna Quantification From Viable Conidia Using the Pma-qpcr Tementioning
confidence: 99%
“…All solvents were HPLC grade and all chemicals were analytical grade. Method performance characteristics for AOH and AME are detailed in Estiarte et al (2016).…”
Section: Dna Quantification From Viable Conidia Using the Pma-qpcr Tementioning
confidence: 99%